PENERAPAN METODE SEARCH ENGINE OPTIMIZATION (SEO) SISTEM INFORMASI AKADEMIK (STUDI KASUS: SMA MUHAMMADIYAH 3 PALEMBANG) - Evi Yulianingsih (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
The study was conducted at SMA Muhammadiyah 3 Palembang, this time the schools have not implemented the Academic Information System so as to find out the available information about the new student of the school and the community must come directly to school and the information provided was incomplete for the researchers want to create a System Information WEB based academic by applying methods of Search Engine Optimization with this method will facilitate the public to find the information they need about the school because this method uses keywords directly to the desired information. The method used in the development of this software is the Waterfall method. The goal of this research is to produce a website Academic Information System which aims to provide information about the school Muhammadiyah 3 Palembang and to develop this system in the future expect this school to increase the number of new students.